2014
DOI: 10.1021/jp407820a
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Co and Ni on Graphene with a Double Hexagonal Symmetry: Electronic and Magnetic Properties

Abstract: Inspired by Lie symmetries, we study the electronic and magnetic properties of cobalt (Co) and nickel (Ni) adatom adsorption on the graphene material using density functional theory calculations. The system we consider here consists of a static single layer of graphene interacting with transition-metal (TM) atoms. This system shows a nice geometrical shape having a double hexagonal structure appearing in the G 2 Lie algebra. This structure is associated with 25% concentration corresponding to a coverage of 0.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…The fundamental properties of transition‐metal‐adsorbed graphene systems are fully explored under the various adatoms, concentrations and distributions. Based on the completely calculated results, transition metals are preferably adsorbed at the hollow‐site compared to the top‐ and bridge‐sites, which is consistent with previous theoretical predictions . The adatom distribution of transition metals on a graphene surface could be examined by experimental measurement, for which STM is an efficient tool.…”
Section: Geometric Electronic and Magnetic Propertiessupporting
confidence: 86%
See 2 more Smart Citations
“…The fundamental properties of transition‐metal‐adsorbed graphene systems are fully explored under the various adatoms, concentrations and distributions. Based on the completely calculated results, transition metals are preferably adsorbed at the hollow‐site compared to the top‐ and bridge‐sites, which is consistent with previous theoretical predictions . The adatom distribution of transition metals on a graphene surface could be examined by experimental measurement, for which STM is an efficient tool.…”
Section: Geometric Electronic and Magnetic Propertiessupporting
confidence: 86%
“…[17][18][19][20] These systems have been reported to exhibit magnetism and other interesting properties that are promising for spintronic devices and batteries. [21][22][23] The aim of our present work is to investigate the transition metal-enriched fundamental properties of monolayer graphene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that these metal nanoparticles can be uniformly decorated on graphene surface without forming any carbides [32][33][34] . The graphene-metal hybrids have been found to be highly stable in terms of particle size as a function of reaction time, temperature and reaction between graphene and metal nanoparticles (see supporting information).…”
Section: Microstructural Characterizationmentioning
confidence: 99%
“…Accordingly, the principal hexagonal unit cell has now in all 12 atoms leading to (1×1) and ( √ 3 × √ 3)R30 • superstructures on the two parallel sheets divided by a length distance fixed by the relaxation method. Thanks to the use of WIEN2K code whose basis is on the DFT method [19,20], the properties of the double hexagonal material have been computed or worked out. It is worth noting here that these properties are electronic and magnetic.…”
Section: Introductionmentioning
confidence: 99%